Oxidized chondroitin sulfate eye drops ameliorate the prognosis of fungal keratitis with anti-inflammatory and antifungal effects. Issue 38 (7th September 2022) - Tian, Xue; Peng, Xudong; Long, Xiaojing; Lin, Jing; Zhang, Yingxue; Zhan, Lu; Zhao, Guiqiu
Abstract : Oxidized chondroitin sulfate (OCS) eye drops was prepared by oxidizing chondroitin sulfate (CS) with sodium periodate (NaIO4 ). OCS treatment improved the prognosis of A. fumigatus in mice by reducing corneal fungal load and regulating inflammation. Abstract : Fungal keratitis (FK) is a refractory ophthalmic disease that can result in vision impairment and even blindness due to the severe fungal invasiveness and excessive inflammatory response. Therefore, antifungal treatment combined with local immunosuppressive therapy is regarded as the most effective strategy to improve the clinical outcome of FK. Oxidized polysaccharides with aldehyde groups possess obvious inhibitory activity towards microorganisms. Herein, we use chondroitin sulfate (CS), a recognized anti-inflammatory biopolysaccharide, to prepare oxidized chondroitin sulfate (OCS) via sodium periodate (NaIO4 ) oxidation for the treatment of FK. The chemical structure of OCS was characterized by FTIR, 1 H NMR, and XPS, revealing that the O -dihydroxy in the d -glucuronic acid unit of CS was selectively broken by NaIO4, forming active aldehyde groups. The introduction of aldehydes not only retains the anti-inflammatory activity but also confers OCS with antifungal property. In vitro antifungal experiments showed that OCS inhibits the growth, represses the biofilm formation and alters the membrane integrity of A. fumigatus . The toxicity of OCS was evaluated by cytotoxicity tests (CCK-8) and the Draize eye test in vitro and in vivo . qRT-PCR confirmed that OCS had similar anti-inflammatory activity as CS. In mice with A. fumigatus keratitis, OCS versus CS or PBS showed an excellent therapeutic effect, characterized by a lower corneal inflammation score, less fungal load, reduced neutrophil recruitment, and the downregulated expression of pro-inflammatory factors. Our findings demonstrate that OCS improves the prognosis of A. fumigatus keratitis in mice by inhibiting the growth of fungi, reducing the recruitment of neutrophils and inhibiting the inflammatory response. It provides innovative ideas for the development and application of OCS in medicine and biomaterials fields.